Pemberian Ganti Rugi Oleh Pemerintah Akibat Pembangunan Jalan Tol Kediri-Tulungagung - Ramadani Dimas Pamungkas; Deandra Myana Rahayu; Syafa Nabila Azzahra; Fadia Amanda Pertiwi; Hany Nurpratiwi (Journal of Creative Student Research, 2023)
The objectives of the National Agrarian Law are in line with the objectives of the 1945 Constitution of the Republic of Indonesia as the legal foundation for the formation of the UUPA, namely "to protect the entire Indonesian nation, promote public welfare, educate the nation's life, and participate in carrying out world order based on freedom, eternal peace." and social justice”. Before there were clear rules governing land issues, many land conflicts occurred. One type of conflict that often occurs is between the state and the community regarding Nation Land Tenure Rights representing the public interest, and then private property ownership, which then results in social inequality that arises in society. social. In the compensation paradigm itself, it tends to mean that the holder of land rights has experienced a loss prior to the release of his land for public use. Presidential Decree No. 55 of 1993, Presidential Decree No. 36 of 2005 and Presidential Decree No. 65 of 2006 contain many weaknesses and are repressive in nature which harm land rights owners. Various cases of community welfare land acquisition development show various problems that arise in the implementation process. With the promulgation of Law Number 2 of 2012, the government is trying to correct deficiencies in the previous laws and regulations regarding land acquisition for public purposes. Compensation for Land Acquisition Since the promulgation of Law Number 2 of 2012, the government has assessed the value of compensation for each plot of land, including land, space above ground and basement, buildings, plants and land, for public purposes; and/or other things that can be assessed as Loss. The amount of compensation determined by the appraiser based on the results of the assessment becomes the basis for negotiating and determining losses.